The Effect Of Flavor Innovation And Grilled Rib Presentation Strategies On Consumer Purchase Interest At Restaurant Blowing In Karanganyar City, Central Java - Lokosari, Keken; Nurlaela, Luthfiyah (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The shift in eating behavior towards a multisensory experience means that purchasing interest is no longer determined by taste alone, but also by flavor innovation and presentation strategies. This study aims to assess the effect of flavor innovation and presentation strategies, as well as both simultaneously, on the purchasing interest in grilled ribs at Blowing Restaurant, Karanganyar. The research method used in this study is explanatory quantitative. The sample size used was 31 respondents. The data collection technique used was a questionnaire using a 4-point Likert scale. The analysis technique used in this study was multiple linear regression. The results showed that flavor innovation had a significant positive effect on purchasing interest; presentation strategy had a significant effect; and both simultaneously increased purchasing interest. The suggestion that can be conveyed is to combine innovative flavors (andaliman for uniqueness, taliwang for authenticity) with multisensory presentation (anglo for warmth/authenticity, hot plate for audio-aroma effects) supported by attractive product narratives. Future research is recommended to use a controlled experimental design and link purchase intent with actual sales results. Theoretically and pedagogically, this research contributes as an empirical example of the application of the concept of multisensory experience in culinary product development, which can be used as teaching material in entrepreneurship education, marketing management, and culinary vocational education.